Crisis conformity as affiliation defense under mortality salience: a TMT perspective - Lu, Kexin; Gao, Yang; Ni, Yichen; Li, Hong (Frontiers in Psychology, 2025)
BackgroundDuring crises, individuals often exhibit elevated conformity, as evidenced by crowding, stampedes, and hoarding; however, the mechanisms driving this behavior remain underexplored. As Terror Management Theory suggests, behaviors that intensify after mortality salience serve as existential defenses. Drawing on TMT, this study posits that crisis-induced conformity arises as a defense against death anxiety. Coupled with evidence that conformity fulfills the fundamental need for affiliation, this research hypothesizes that conformity specifically functions as an affiliation defense through which individuals mitigate death-related anxiety in life-threatening contexts.MethodFour experiments were conducted to test the proposed three hypotheses. Study 1a employed scenario-based priming (crisis vs. daily situations) and self-report measures to investigate the elevated affiliation needs and conformity as affiliation defenses at two levels, in line with the mortality salience hypothesis. Study 1b used an improved TMT paradigm, replacing neutral controls with economic crisis manipulations to isolate existential threats from nonspecific emotional arousal. Study 2 elucidates the relationship between affiliation needs and conformity propensities in crisis contexts by investigating how experimental manipulation of affiliation influences conformity. Study 3 used a 2 (situation: crisis/control) × 2 (conformity/non-conformity) design to investigate the anxiety-buffering function of conformity.ResultsBoth Study 1a and 1b showed that crises significantly increased both affiliation needs and the tendency toward conformity. Study 2 revealed that the presence of dyadic companions during a crisis significantly attenuates individuals’ affiliation needs toward crowds, while conformity propensities also significantly diminish. Study 3 found that crisis conformity reduced negative affects and increased positive emotions compared to non-conformity, while no such effects emerged in daily contexts.ConclusionThese findings reveal the psychological mechanism of crisis conformity within the framework of TMT: crises increase affiliation needs and conformity (Studies 1a & 1b), consistent with the mortality salience hypothesis. The presence of evacuation companions during mortality-salient crises significantly attenuates affiliative needs toward crowds and correspondingly reduces conformity propensities (Study 2). Conformity as an affiliation defense mitigates negative affect and mortality anxiety while enhancing positive affect, thereby buffering psychological distress (Study 3). This study extends TMT to the field of crisis conformity research, providing a new perspective on interpreting the intrinsic motivation underlying crisis conformity.